PROGRAM PENGENALAN MAKANAN BERGIZI PADA ANAK USIA DINI MELALUI MEDIA PEMBELAJARAN AUDIO VISUAL DI DESA PINOGU KABUPATEN BONE BOLANGO - Anita Lasulika (Kreasi: Jurnal Pengabdian Masyarakat, 2021)
The problem discussed in this classroom action research is how audio-visual learning media can increase understanding about nutritious food in early childhood at Dahlia Kindergarten, Pinogu Village, Pinogu District, Bone Bolango Regency, Gorontalo Province, totaling 25 children, consisting of 11 boys boys and 14 girls. In this study, researchers focused on three indicators in introducing nutritious food: knowing the types of nutritious food, grouping the types of nutritious food, and knowing the benefits of nutritious food. The method used in this research is the descriptive method of Classroom Action Research (PTK), with research procedures consisting of: preparation, implementation, observation, evaluation, and analysis and reflection. The implementation of this research consisted of two cycles. Each cycle carries out two actions. The results of pre-cycle observations reached 30% completeness, in cycle I the level of learning completeness was 44%, and in cycle II there was an increase of 82%. So it can be concluded that audio-visual learning media can increase children's understanding of nutritious food, and can increase children's enthusiasm in the learning process in group B at Dahlia Kindergarten, Pinogu Village, Pinogu District, Bone Bolango Regency, Gorontalo Province.